CENTRALIZED AND DECENTRALIZED SECURITY MANAGEMENT MODELS: ORGANIZATIONAL CHOICE AND STRATEGIC APPLICABILITY: CENTRALIZED AND DECENTRALIZED SECURITY MANAGEMENT MODELS: ORGANIZATIONAL CHOICE AND STRATEGIC APPLICABILITY - Metodieva, Tsvetelina (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This study examines the advantages, disadvantages, and applicability of centralized, decentralized, and hybrid security management models in contemporary organizations. Based on a comparative analysis and an organizational maturity-based approach, a framework for strategic model selection is proposed. The study highlights the importance of adaptability and integration between central control and local responsibility, especially in the context of modern cyber threats, globalization, and regulatory requirements [1,2].